BAHAYA INFEKSI HIV (BUMAN IMMUNODEFICIENCY VIRUS) BESERTA ALTERNATIF PEMECAHANNYA - Senam Senam (LPMPP Universitas Negeri Yogyakarta, 1999)
The virus called HIV can infect human cells andcause the disease called AIDS. HIV infection is principallythe integration between the DNA of the HIV andthat of the host cell so that the DNA of the HIV undergoesreplication at the time the host cell undergoes fission.The HIV is unable to conduct a metabolism processwithout any host cell. In order to survive, the HIVmakes use of the energy, precursor molecules, and essentialenzymes of the host cell. The competition occurringbetween the HIV and the host cell will result inthe host cell's growth b,eing disturbed. Human cellswhch can be infected by the HIV include the T helperlymphocyte cells, the macrophage cells, and the dendriticcells. The T helper lymphocyte cells play a partin the biosynthetic process of antibodies. The macrophagecells are very useful in the protection of cellsfrom infection caused by a number of pathogenousmicroorganisms as well as toxic chemical substances.The dendritic cells function as the cells providing antigensas well as the cells complementingthe T cytotoxiccells. The three types of cells above are responsible forthe body's immunity system. The occurrence of H V-infection on these cells causes a decline in the humanbody's immunity system and results in AIDS. The contagonof HIV can happen via sexual intercourse (heterosexualor homosexual), blood transfusion, the use ofthe same needle for injections to different persons, andsaliva. Prevention of HTV infection can be done byavoiding the behaviors described above whle for curativetreatment can possibly be done by gving antibioticswhich can hinder the biosynthetic process of thereverse transcriptase enzyme protein and decrease theactivity of the enzymes playing a part in the modificationprocess of a foreign DNA. In social life, ostracismon the IW carrier is not approved because the conta-@on of ttus virus is not via air, the slun, or clothes.